Differential Blood-Brain Barrier Transport and Cell Uptake of Cyclic Peptides In Vivo and In Vitro - Erik Melander; Camilla Eriksson; Sara Wellens; Kimia Hosseini; Robert Fredriksson; Fabien Gosselet; Maxime Culot; Ulf Göransson; Margareta Hammarlund-Udenaes; Irena Loryan (MDPI AG, 2023)
The blood-brain barrier (BBB) poses major challenges to drug delivery to the CNS. SFTI-1 and kalata B1 are cyclic cell-penetrating peptides (cCPPs) with high potential to be used as scaffolds for drug delivery. We here studied their transport across the BBB and distribution within the brain to gauge the potential of these two cCPPs as scaffolds for CNS drugs. In a rat model, SFTI-1 exhibited, for a peptide, high extent of BBB transport with a partitioning of unbound SFTI-1 across the BBB, Kp,uu,brain, of 13%, while only 0.5% of kalata B1 equilibrated across the BBB. By contrast, kalata B1, but not SFTI-1, readily entered neural cells. SFTI-1, but not kalata B1, could be a potential CNS delivery scaffold for drugs directed to extracellular targets. These findings indicate that differences between the BBB transport and cellular uptake abilities of CPPs are crucial in the development of peptide scaffolds.